(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2011)
Rheumatoid arthritis (RA) is the commonest joint disease with considerable morbidity and mortality. Conventional disease modifying antirheumatic drugs like methotrexate form the cornerstone of therapy. These drugs have several limitations in terms of slow onset of action, adverse effects and modest remission rates. Several cytokines are involved in the pathogenesis of RA. Biological agents that specifically inhibit the effects of tumour necrosis factor-alpha (TNF-a) or interleukin-1 (IL-1) represent a major advancement in the treatment of RA. By targeting mediators that are directly involved in the pathogenesis of RA, these agents slow the radiological progression of bone and cartilage damage in joints, prevent or delay the onset of disability. These are highly specific and better tolerated. The use of these biological agents needs careful monitoring for side effects, including the development of infection. Additional anti-cytokine agents for the treatment of RA are under further development. Key words: Rheumatoid arthritis; biological agents; inflammatory cytokine. DOI: 10.3329/jbsp.v29i1.7168 J Bangladesh Coll Phys Surg 2011; 29:27-31